Using an Ombudsman to Oversee Public Officials - Manning, Nick; Galligan, D.J. (World Bank, Washington, DC, 2012)
The note addresses the role of ombudsman offices, and what ensures its effectiveness. Good administration requires much more than acting legally, which include constitutional, and human rights abuses, mismanagement, as well as illegal practices. An ombudsman's independence from other branches of government, and administration, particularly the executive branch, is a crucial factor, following the legal provisions on its appointment, dismissal, powers, and budgetary issues. Though closely associated with parliament because courts are important autonomous regulators of official behavior, there is the potential to overlap with an ombudsman. But, to the extent that the ombudsman becomes involved in matters of legality, it is an adjunct to the courts. Conditions for an effective ombudsman are: political support; adequate resources; public perception, functional competence; and, regulatory value.